The Muslim intelligentsia's aspiration for an Islamic University: initial concept and philosophical foundation - Hassan, Mohd. Kamal (IIUM Press, 2009)
Introduction : The desire to have an Islamic University in Malaysia was part of the Muslim-Malay intelligentsia's dream in their peaceful struggle for the advancement of Islamic education in the pre-independence Federation of Malaya (which included the island of Singapore). The establishment of Kolej Islam Malaya (the Islamic College of Malaya) in Kelang, Selangor, in 1955, two years before independence, was supposed to realize the birth of an Islamic university, similar to Al-Azhar, as desired by the original promoters, who were mainly in Singapore, but the lack of realistic planning coupled with other unforeseen shortcomings forced the promoters to be contented with the College-level education first, in the hope that an Islamic university would eventually be established in the not too distant future. 1 The leadership, the academic staff of the College and its students continued to advocate and press for the establishment of the Islamic university in the post-Independence period but the federal government had other priorities then.